INFORMATION TECHNOLOGIES IN ENGLISH CLASSES - Kaipbergenova, F.T. (SCIENCE and SOCIETY, 2019)
The rapid development of information and communication technologies generates a number of radical changes in our lives, including in the educational process. The positions of the English language in the world as the leading means of international communication are associated primarily with the rapid development of high technologies, economics, and PR - technologies.